Trends in the developments of financial reporting approach and its implication on accounting educators / Sharifah Norhafiza Syed Ibrahim and Yusri Arshad - Syed Ibrahim, Sharifah Norhafiza; Arshad, Yusri (2013)
Accounting is the heart of business. It is the language for business where it provides essential business Information for making important economic decisions. The framework for financial reporting is based on the dominant financial reporting approach. This approach is initially derived from generally acceptable accounting practices. Accounting practitioners form accounting professional bodies which collectively set accounting standards in pursuit of enhancing the quality of accounting information. The development of financial reporting approach is influenced by the evolution of business entities. When people first trade, they operate as sole entrepreneurs. Therefore, they only need accounting to calculate income or loss. At that time financial accounting approach is based on profit and loss approach where expenses are matched against income in order to determine whether the business is making profit or loss. 14ny accrued expenses and unexpired assets are reported in the balance sheet. In other words, a balance sheet is merely by-product of the profit and loss account. Accounting educators are trained to teach students related accounting concepts such as definitions of income and expenses, matching concept, conservatism and specific methods of calculating and presenting income and expenses. However, businesses grow into larger entities that call for the establishment of companies and group companies, thus, assessing the value of companies are becoming more important. Hence, the emphasis is now shifted to a balance sheet and the financial reporting approach is considered to be more balance sheet based. Now, accounting educators need to ensure students are familiar with identification, classification, measurement and presenting elements of a statement offinancial position, namely, assets and liabilities. This paper provides some empirical evidence of an increasing dominance of a balance sheet based financial reporting approach and its implication on accounting educators.